2013
DOI: 10.1074/jbc.m113.471425
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Acinar Cell Nuclear Factor κB Activation Because of Bile Acid Exposure Is Dependent on Calcineurin

Abstract: Background: Bile acids cause activation of NF-B and lead to injury in pancreatic acinar cells, but the mechanism is unknown. Results: Pharmacologic and genetic inhibition of calcineurin reduces bile acid-induced NF-B activation and PKC-␦ translocation. Conclusion: Calcineurin facilitates bile-induced NF-B activation. The mechanism is at the level of PKC activation. Significance: We have identified a novel mechanism by which bile acids facilitate NF-B activation in pancreatic acinar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 81 publications
0
25
0
Order By: Relevance
“…Further, the shape of the Ca 2+ signal in most cells mimicked a high amplitude peak plateau, which is a characteristic pathological signal that precedes acinar cell injury and pancreatitis 25, 26, 4853 and which would favor calcineurin activation 54 . A recent report demonstrated that a long incubation (of 4 hr) with ioversol, a RC that is similar to the iohexol and iopamidol we used, caused a slow, globalized increase in baseline cytosolic Ca 2+ levels in the NRK-52E renal cell line 55 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Further, the shape of the Ca 2+ signal in most cells mimicked a high amplitude peak plateau, which is a characteristic pathological signal that precedes acinar cell injury and pancreatitis 25, 26, 4853 and which would favor calcineurin activation 54 . A recent report demonstrated that a long incubation (of 4 hr) with ioversol, a RC that is similar to the iohexol and iopamidol we used, caused a slow, globalized increase in baseline cytosolic Ca 2+ levels in the NRK-52E renal cell line 55 .…”
Section: Discussionmentioning
confidence: 94%
“…Among the putative targets of Ca 2+ in pancreatitis, which include the MPTP and kinases, the Ca 2+ -activated serine/threonine phosphatase calcineurin has been implicated as a critical mediator of acinar injury and pancreatic inflammation 16, 38, 53, 58, 59 . Calcineurin is a dimer formed by a catalytic A subunit (CnA) and a regulatory B subunit (CnB) 60–62 .…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that the NF-B-dependent pathway is critical in the development and persistence of pancreatic inflammation and injury (36,(41)(42)(43)(44). Thus, NF-B is an attractive target for pharmacological intervention and being able to monitor the NF-B-dependent pathway under various pathological states would facilitate the validation of novel therapeutic agents and approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several targets of aberrant acinar cell Ca 2ϩ following bile acid exposure have been suggested and include mitochondria (44,45), sarco/endoplasmic reticulum Ca 2ϩ -ATPase (SERCA) pumps (7), and a host of Ca 2ϩ -mediated proteins (28,42). We have shown that the serine/ threonine phosphatase calcineurin is activated in response to Ca 2ϩ generated by bile acid exposure (42) and that calcineurin plays an important role in regulating bile acid-induced NF-B activation (46).…”
Section: Discussionmentioning
confidence: 99%